Bio-organic fertilizers reshape rhizosphere bacterial community and enhance crop productivity in reclaimed soil - Yang, Jing; Lu, Xiaomin; Hao, Bing; Wang, Shimei; Kong, Lijuan; Shao, Qingqin; Li, Weiping; Wang, Xingyu; Xu, Youzun; Wu, Wenge; Wang, Jianfei; Yan, Lei; et al. (Frontiers in Microbiology, 2025)
Bacillus amyloliquefaciens-modified bio-organic fertilizer (BOF) has shown great potential in improving crop yields and soil quality in degraded or reclaimed soils. However, the underlying microbial mechanisms remain unclear. This study conducted field experiments in reclaimed rice soil to compare the effects of chemical fertilizer (CF), organic fertilizer (OF), and BOF on rice yield and rhizosphere microbial community dynamics. The rice yield of BOF treatment increased by 9.6%, from 7.79 to 8.54 t ha−1 compared with CF, and significantly improved critical soil properties by alleviating acidification, as indicated by an increase in pH from 6.10 to 6.65, achieved a 15.7% rise in organic matter accumulation. Available phosphorus increased by 24.5% and available potassium by 14.4%. High-throughput sequencing revealed that bio-organic fertilizer application markedly altered rhizosphere bacterial communities, enriching sulfur-oxidizing taxa and beneficial plant-associated genera including Sphingomonas. Quantitative analysis indicated a significant positive correlation between the abundance of B. amyloliquefaciens and Sphingomonas, and both were associated with improved soil nutrient status and crop performance. Metabolic pathway analysis based on KEGG showed enrichment of the citric acid cycle (1.8-fold) and amino acid biosynthesis (2.3-fold) pathways, which promote nutrient mobilization and microbial interactions. These findings provide new insights into the synergistic interactions between introduced bacteria and native bacterial communities and establish a mechanistic foundation for designing targeted microbial formulations to promote sustainable rice production in improved soils.